In situ nutrient degradation of conventional diets commonly fed to dairy cows in central Myanmar - Aung, Min (Journal of Aridland Agriculture, 2016)
The determination of nutrient degradability is very important for the effective use of feeds in ruminant production. Therefore, this experiment was conducted to determine the nutrient degradability and energy protein synchronization of conventional diets commonly fed to dairy cows in the central Myanmar through the in situ method. The conventional diets are Diet-ST (diet from Sin Tel), Diet-MN (diet from Myay Ngu), Diet-TP (diet from Ta Pel) and Diet-AM (diet from Amarapura). The roughage to concentrate ratio of conventional diets ranged from 53:47 to 72:28. The crude protein (CP) content of Diet-TP (17.96%) was significantly higher (p<0.05) than those of other diets with the least CP obtained from Diet-AM (11.46%). Among the conventional diets, wide variation of dry matter (DM) and organic matter (OM) disappearances were observed throughout the incubation times. The highest value (p<0.05) was found in Diet-AM and the lowest (p<0.05) was observed in Diet-ST and Diet-TP. The rapidly degradable fraction â€œaâ€ and rate of degradation â€œcâ€ of DM and OM of Diet-AM was significantly higher (p<0.05) than those of other diets. The effective degradability of DM and OM were also highest (p<0.05) in Diet-AM. Generally, the lowest (p<0.05) CP disappearance was observed in Diet-TP. The rapidly degradable fraction â€œaâ€ of CP was highest (p<0.05) in Diet-ST and the greater (p<0.05) effective degradability was observed for Diet-AM. Moreover, the highest values (p<0.05) of rumen degradable protein (RDP), rumen undegradable protein (UDP) and energy protein synchronization were found in Diet-TP, while the lowest value was observed in Diet-AM. Therefore, it was concluded that all conventional diets could be used as ration for dairy cows; however, the best potential was found in Diet-AM because of its highest effective degradability of nutrients.